PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILITAS DAN RASIO AKTIVITAS TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2016 – 2022) - Octavia, Anita Dwi; Rosdiana, Riska (Journal of Fundamental Management (JFM), 2025)
This study aims to examine and analyse the effect of firm size, liquidity, profitability, and activity ratios on firm value of consumer non-cyclicals sector listed on the Indonesia Stock Exchange. Research data is the annual data for the 2016-2022 observation period obtained from the company's annual report. The sampling method used is purposive sampling. The analytical method used in this study is panel data regression with the selected model approach Fixed Effect R2 value of 83.39 percent. The results showed that firm size has a negative effect on firm value, liquidity, and activity ratios had no effect on firm value, while profitability has a positive effect on firm value. (Keywords:  Firm Size, Current Ratio (CR), Return On Equity (ROE), Total Aset Trunover (TATO) and Firm Value)